Development of a Flipbook Learning Media Based on a Problem-Based Learning Model to Improve Mathematical Literacy Skills and Students' Motivation for Learning on the Pythagorean Theorem in Grade VIII at State Junior High School 40 Medan - Simarmata, Putri Sonia; Mulyono, Mulyono; Lubis, Asrin; Nasution, Hamidah (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2025)
Based on the results of initial observations at SMP Negeri 40 Medan, there are teachers who have not maximized the design, development, and utilization of learning media, especially flipbook media that has never been implemented. As well as the mathematical literacy skills and learning motivation of students are still low. This study aims to (1) produce flipbook media based on the Problem Based Learning learning model that is valid, practical and effective, (2) analyze the improvement of mathematical literacy skills and (3) analyze the improvement of student learning motivation using flipbook media based on Problem Based Learning. This study uses the ADDIE model. This study involved class VIII students of SMP Negeri 40 Medan. The instruments used in the development of flipbook media are Teaching Modules, LKPD, Mathematical Literacy Ability Tests and Student Learning Motivation Questionnaires. The results of the study are that the flipbook media meets the valid criteria with a score of 4.69, then the flipbook media was tested to obtain practical and effective media so that it meets the practical criteria with a score of 88.95, and the flipbook media meets the effective criteria with a score of 87.79. The increase in mathematical literacy skills measured by N-gain on the development trial conducted twice against pretest with posttest I with an average N-gain of 0.33 in the medium category, then against posttest I and posttest II with an average N-gain of 0.73 in the high category. Furthermore, the increase in students' learning motivation by measuring the pretest and posttest with an average N-gain of 0.6 in the medium category. Based on the N-gain results, it is stated that flipbook media based on the Problem Based Learning learning model is able to improve students' mathematical literacy skills and learning motivation at SMP Negeri 40 Medan.